Meta-analysis of the efficiency and safety of neoadjuvant therapy with immune checkpoint inhibitors in resectable hepatocellular carcinoma - Tuersun, Adili; Mohetaer, Munire; Hou, Guanxin; Cheng, Gang (Frontiers in Medicine, 2025)
PurposeImmunotherapy as a neoadjuvant treatment approach has achieved certain therapeutic effects in various types of cancer. However, in the specific cancer type of hepatocellular carcinoma (HCC), standardized protocols for neoadjuvant immunotherapy remain to be defined. This systematic review and meta-analysis focus on evaluating the efficacy and safety of neoadjuvant immunotherapy in the treatment of HCC, aiming to provide a robust basis for clinical decision-making.MethodsThis study systematically searched databases such as PubMed, EMBASE, the Cochrane Library, and conference proceedings to identify clinical trials focusing on patients with HCC undergoing neoadjuvant immunotherapy. The Review Manager 5.4 software was applied to estimate the odds ratio (OR) of effect sizes and their corresponding 95% confidence intervals (CI).ResultsImmune checkpoint inhibitors (ICIs) demonstrate significant efficacy in improving pathological outcomes and safety profiles in patients with resectable hepatocellular carcinoma (HCC). Specifically, ICIs significantly increase the pathological complete response (pCR) rate (OR = 0.23, 95% CI [0.14, 0.37], p < 0.00001) and major pathological response (MPR) rate (OR = 0.47, 95% CI [0.32, 0.70], p = 0.0002). They also markedly enhance the objective response rate (ORR) (OR = 0.42, 95% CI [0.28, 0.63], p < 0.0001). Furthermore, ICIs potentially improve the surgical resection rate (OR = 3.91, 95% CI [2.05, 7.45], p < 0.0001) and reduce the incidence of grade 3–4 treatment-related adverse events (TRAEs) (OR = 0.27, 95% CI [0.17, 0.44], p < 0.00001), indicating both therapeutic benefits and acceptable toxicity profiles.ConclusionNeoadjuvant immunotherapy shows promise in the treatment of resectable HCC. Nonetheless, to further validate its efficacy, more large-scale, well-designed clinical trials are necessary to provide conclusive evidence.Systematic review registrationThis comprehensive review adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) standards and has been carried out as per a preregistered protocol (PROSPERO registration number: CRD42024560660).